2017
DOI: 10.4251/wjgo.v9.i2.78
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of vascular endothelial growth factor polymorphisms in colorectal cancer patients

Abstract: AIMTo investigate the associations of the genetic polymorphisms of vascular endothelial growth factor A (VEGF-A) -1498C>T and -634G>C, with the survival of patients with colorectal cancer (CRC).METHODSA prospective cohort consisting of 131 Brazilians patients consecutively operated on with a curative intention as a result of sporadic colorectal carcinoma was studied. DNA was extracted from peripheral blood and its amplification and allelic discrimination for each genetic polymorphism was performed using the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Hypoxia (≤3% oxygen) and anoxia (≤0.3% oxygen) are potent drivers of cancer cell proliferation, angiogenesis, metastatic potential and resistance to chemo-and radio-therapy (108). The induction and activation of the hypoxia-inducible transcription factor HIF1A and the HIF target of vascular endothelial growth factor alpha (VEGFA) are separately associated with poor CRC clinical outcome (109,110).…”
Section: Sexual Dimorphism and The Tumor Microenvironment In Crc Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia (≤3% oxygen) and anoxia (≤0.3% oxygen) are potent drivers of cancer cell proliferation, angiogenesis, metastatic potential and resistance to chemo-and radio-therapy (108). The induction and activation of the hypoxia-inducible transcription factor HIF1A and the HIF target of vascular endothelial growth factor alpha (VEGFA) are separately associated with poor CRC clinical outcome (109,110).…”
Section: Sexual Dimorphism and The Tumor Microenvironment In Crc Hypoxiamentioning
confidence: 99%
“…Hypoxia (≤3% oxygen) and anoxia (≤0.3% oxygen) are potent drivers of cancer cell proliferation, angiogenesis, metastatic potential and resistance to chemo- and radio-therapy ( 108 ). The induction and activation of the hypoxia-inducible transcription factor HIF1A and the HIF target of vascular endothelial growth factor alpha (VEGFA) are separately associated with poor CRC clinical outcome ( 109 , 110 ). Functional cross-talk between GPER activation and EGF signalling has been demonstrated in CRC ER-negative cell lines and modulates the potential for CRC cell proliferation and migration ( 111 ).…”
Section: Sexual Dimorphism and The Tumor Microenvironment In Crcmentioning
confidence: 99%
“…Several previous observational studies have found that polymorphisms in VEGF may predispose patients to colorectal cancer susceptibility ( Kim et al, 2008 ; Zhao et al, 2012 ; Jang et al, 2013 ; Espírito Santo et al, 2017 ; Yang et al, 2017 ). Jang et al studied 882 participants in the Korean population, including 390 colorectal patients and 492 controls.…”
Section: Discussionmentioning
confidence: 99%
“…• Another prospective study of CRC patients aimed to investigate the correlation between genetic polymorphism of VEGF-A with survival using the DNA extracted from peripheral blood. In a univariate analysis, there was a significant association (OR = 0.32; p = 0.048) between genotype CC of the VEGF-A -1498C>T polymorphism and the presence of CRC liver metastasis [70].…”
mentioning
confidence: 95%